Understanding the Implications of Marriage Law Amendments: Marriage Dispensation Cases in Indonesian Religious Courts - Yetta, Yasin; Rajafi, Ahmad; Subeitan, Syahrul Mubarak (Institut Agama Islam Negeri Curup, 2024)
This article aims to determine the implications of changing Law Number 1 of 1974 to Law Number 16 of 2019 concerning Marriage Dispensations in Indonesian Religious Courts. Specifically, this research seeks to analyze the increase in cases of post-amendment dispensation and explore the factors contributing to the gap between legal mandates and community practices regarding early marriage. This research uses a qualitative approach with a juridical perspective using comprehensive data analysis from Religious Courts in various regions in Indonesia. The data sources include decisions from the Directory of Decisions of the Supreme Court of the Republic of Indonesia, which focus on requests for dispensation. The analysis involves data collection, selection, sorting, reduction, and conclusion, aiming to effectively meet research objectives and address research gaps. This study integrates legal norms and societal dynamics to comprehensively understand the failure of the Amendment and its implications for the marriage dispensation in Indonesia. The analysis revealed a significant increase in requests for dispensation after the amendment. This reflects the challenges in dealing effectively with early marriage. Cultural pressures, institutional inconsistencies, and societal complexity contribute to the rise in cases of dispensation, underscoring the need for a different approach to legal reform and societal practice. Despite efforts to equalize the marriage age and prevent early marriage, the Amendment has not effectively addressed societal realities, resulting in a gap between legal mandates and actual practice.